Konstruksi Nilai-Nilai Perempuan Metropolis Indonesia Dalam Majalah Femina - Dian Swandayani; Nuning Catur Sri Wilujeng (Jurnal Pendidikan dan Kebudayaan, 2010)
The subject of this research is rubric of â€œWaktu Senggangâ€ or Leisure Time in Femina magazine in 2007. The objectives of the research are revealing all kinds of films, music, books which bend the values of metropolis womenâ€™s images and social constructs. Data collecting is conducted through intensive lecture, reading documentation, then categorizing the data. The data, then, analyzed in qualitative descriptive method. The result of the research shows that: 1) the films issued and reviewed in the rubric of â€œWaktu Senggangâ€ in Femina magazine in 2007 are dominated by Hollywood movies; 2) the music genre in the same rubric are mostly pop music with male leading vocal; 3) the books that dominate the rubric are novel or memoir/ biography, which women as the principle character and their problems. The choice on the genre of show, music album, and the reader books reflects an especial female society, which is the metropolis women whom the trend setter is American metropolis women. The choice is not only to determine the self-image of Femina as a female magazine but also to construct a social form that create the taste or the image of the readers as to be the metropolis women, who are different from uneducated country women.Â ABSTRAKSubjek penelitian ini adalah rubrik â€œWaktu Senggangâ€ majalah Femina tahun 2007. Tujuan penelitian ini mengungkapkan secara keseluruhan jenis-jenis film, musik, buku bacaan yang membentuk nilai-nilai citra perempuan metropolis dan kontruksi sosial. Pengumpulan data dilakukan melalui teknik baca-catat yang dikategorisasi, diinterpretasi dan dianalis secara deskriptif-kualitatif. Hasil penelitian menunjukkan bahwa: 1) film-film yang terdapat dalam rubrik â€œWaktu Senggangâ€ dalam majalah Femina edisi tahun 2007 kebanyakan berupa film-film drama Hollywood; 2) jenis-jenis musik yang terdapat dalam rubrik ini adalah musik-musik pop penyanyi laki-laki; 3) jenis-jenis buku bacaan yang terdapat dalam rubrik ini berupa novel atau memoar/biografi dengan perempuan sebagai tokoh utamanya dan problematika-nya. Pilihan-pilihan terhadap jenis tontonan, album musik, dan buku bacaan tersebut merupakan cerminan dari masyarakat kelompok wanita metropolis dengan metropolis Amerika Serikat sebagai trend-setter. Pilihan tersebut tidak hanya sebagai citra diri majalah Femina tetapi sekaligus juga membentuk atau menjadi formasi sosial dalam membentuk cita rasa atau citra pembacanya sebagai wanita metropolis, bukan wanita kampungan yang tidak berpendidikan.